2020
DOI: 10.3390/en13071701
|View full text |Cite
|
Sign up to set email alerts
|

A PV-Powered TE Cooling System with Heat Recovery: Energy Balance and Environmental Impact Indicators

Abstract: Over the past decades, clean and renewable energy has become a subject of great interest to both science and industry in response to the pollution caused by conventional energy sources. Its useful form should always meet the requirements of high performance and low environmental impact, while remaining within the scope of the expected functionality. The purpose of study presented in this paper was to determine the operational characteristics for a recently developed photovoltaic (PV)-powered thermoelectric (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, these systems are eco-friendly and their GWPs were reported to range from 0.13 to 0.47 gCO2-eq/Wh [90,92]. Therefore, the combined technologies (e.g., thermoelectric cooling systems and PV) are beneficial for solar energy use and environmental protection, meeting the requirements of NZEBs.…”
Section: Solar Energymentioning
confidence: 99%
“…Furthermore, these systems are eco-friendly and their GWPs were reported to range from 0.13 to 0.47 gCO2-eq/Wh [90,92]. Therefore, the combined technologies (e.g., thermoelectric cooling systems and PV) are beneficial for solar energy use and environmental protection, meeting the requirements of NZEBs.…”
Section: Solar Energymentioning
confidence: 99%
“…Figure 4 presents a classification based on these aspects of recent studies addressed in this analysis. Three articles were found involving costs and efficiency in zone A, [27,29,44]; three articles between costs and sustainability in zone B [30,39,46]; one article involving efficiency and sustainability in zone C [36]; and tree articles involving all aspects, costs, efficiency and sustainability in zone U [40,52,56]. From this classification it is concluded that the oxides are inexpensive TE materials with important advantages.…”
Section: Thermoelectric Materialsmentioning
confidence: 99%
“…For this reason, we developed a life-cycle model that includes the emissions of all pollutants and found that PV is much less carbon-intensive than fossil-based power generation. Żelazna and Gołębiowska (2020) [20] analyzed the environmental impact of a PV thermoelectric cooling system with heat recovery capabilities using the principles of material and energy conservation over its life cycle. In contrast to existing studies that almost always use carbon emission factors for the entire life cycle for carbon emission calculations, Pu et al (2021) [21] considered the variability between sub-stages.…”
Section: Research On the Assessment Of Environmental Effects Of Pv Sy...mentioning
confidence: 99%